(untitled) (Fiep Bulletin - online, 2014)
The case study concern the Krakow’s Phenomenon that was directly and personally revealed during UEF A EURO 2012 in Poland and Ukraine. Cracow, despite was excluded from the list of the city that hosted the event, became the mainly actor of the tournament among foreign tourists visiting. The basis for the formulation of this conclusion are the results of the survey realized in Krakow from 9 to 19 June 2012. The mainly goal of the survey was to analize the influece of UEF A EURO 2012 on the decision of the foreign tourist to visit Cracow and their opinion about the city organization for the sport events, like: quality of public services (safety), tourist information, public comunication, Fan zone, easiness of communication with the rest of Europe and the rest of Poland, accomodation and entertainment services.